PERBEDAAN MOTIVASI DAN HASIL BELAJAR IPA PADA SISTEM TRANSPORTASI MANUSIA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEMENT DIVISION (STAD) (SUATU PENELITIAN DI SMP YPPK ST.PAULUS ABEPURA) - Simanjuntak, Ratna; Budiarti, Indah Slamet (Jurnal Ilmu Pendidikan Indonesia, 2013)
The purpose of this study was to determine (1) differences in motivation to learn classroom STDA applied learning model (2) differences in classroom lerning outcomes STDA applied learning model (3) imcreasing mastery of concepts after STDA cooperative learning model. The population in this study were all students of class VIII class with 70 people. The sample used is a sample eighth grade students as a class VII D experiment control class. Collecting data using SPSS version 6. Normality test results show Gain experiment n and n 0,710 0.752 Gain Control, a significant count > 0,05, normal data. Results showed sig homre oenetis count < 0,05, signifakan the two groups had similar or homogenous variance. The results of hypothesis testing ( t test) sig hit < 0,005, reject Ho and accept Ha. The conclusions of this study were (1) there is a difference motivation to learn classroom applied the model type STAD cooperative learning (2) there are differences in learning outcomes applicable class type STAD cooperative learning model (3) there is an increasing mastery of concepts after STAD cooperative learning model. Suggestions that can be extracted is the junior high school teachers should motivate YPPK ST.PAULUS Abepura learn that the results of biological studies students are getting better. Keywords : Type STDA, motivation to learn, learning outcomes, human transport system.